A genetic model defines the importance of the atrial natriuretic peptide receptor (guanylyl cyclase-A) in the regulation of kidney function - Dubois, Susan K. (The National Academy of Sciences, 2000)
Disruption of the atrial natriuretic peptide (ANP) receptor [guanylyl cyclase-A (GC-A)] gene yields mice with a salt-resistant form of hypertension, raising fundamental questions on the role of ANP in acute regulation of the kidney. Here, we show that water intake, food consumption, stool weight, urine volume, and sodium excretion are not significantly different between wild-type and GC-A null mice on standard rodent chow (0.7% NaCl) or a high-salt diet (8% NaCl). In conscious mice with an indwelling catheter, the infusion of a physiological saline solution containing 4% BSA resulted in a marked natriuresis/diuresis in wild-type mice but no response in GC-A null animals. When physiological saline was given by gavage, however, the kidney response of wild-type and null mice was equivalent, raising the possibility that the gastrointestinal tract can directly regulate kidney function. However, administration of 0.9% saline through an intraperitoneal route also resulted in equal kidney responses in wild-type and null mice. When 0.9% NaCl lacking protein was infused i.v., wild-type and null mice both responded at the kidney level. Thus, GC-A appears dispensable for regulation of sodium/water excretion in response to changes in dietary sodium concentration, but likely becomes critical in volume expansions where the isooncotic pressure remains constant, such as head-out immersion or the initial and correctable stages of congestive heart failure.